Kampus Inklusif Ramah Disabilitas: Nyata atau Sebatas Fasilitas? (Lembaga Pengembangan Kinerja Dosen, 2025)
An inclusive, disability-friendly campus is identified as a place that facilitates the higher education needs of people with disabilities by paying attention to usability, convenience, comfort, independence and institutional factors. The government, academics and experts related to inclusive education have developed indicators as criteria for disability-friendly campuses, including academic activities, non-academic activities, social interactions, academic infrastructure, management infrastructure, supporting infrastructure, design, social conditions, physical accessibility , information accessibility, campus institutions, and the role of government. However, the number of students with disabilities is still limited, and there is a tendency that the higher the level of education, the fewer the number of disabled students studying. The aim of this study is to develop indicators or criteria for inclusive, disability-friendly campuses in a more holistic manner so that they can increase the participation of people with disabilities to pursue higher education. The method used in analyzing and formulating strategies is through Focus Group Discussions which involving experts and also related stakeholders. So that it can be seen clearly if there is a gap between the needs of people with disabilities and campus conditions. Furthermore, the analysis was carried out using prospective analysis techniques to determine the key factors that determine interest in continuing higher education, as well as through descriptive analysis to formulate appropriate disability-friendly inclusive campus criteria. The results of the analysis show that among the inclusive indicators of a disability-friendly campus, the key factors are: (1) inclusive campus policies that clearly regulate input-output, (2) commitment to funding support from the government and third parties in funding, and (3) the existence of government commitment to providing scholarships. The government needs to consider further study in determining and establishing minimum standards for assessing disability-friendly inclusive campuses, such as the Disability-Friendly Inclusive Campus Composition Index, the third main indicator of disability-friendly inclusive campuses also needs to be considered.